Hyponatremia associated with Chronic Pituitary Apoplexy Masquerading as SIADH (Bangladesh Critical Care Journal, 2026)
Pituitary apoplexy, while classically acute, can present insidiously as chronic apoplexy, posing significant diagnostic challenges. We report a 60-year-old male with multiple comorbidities who presented with progressive weakness and neck pain following a gastrointestinal illness. He was found to have severe symptomatic hyponatremia (Na+ 115 mmol/L) with a biochemical profile suggestive of the Syndrome of Inappropriate Anti-Diuretic Hormone (SIADH). Brain MRI demonstrated sellar–suprasellar pituitary mass with heterogeneous signal intensity and hemorrhagic components, showing peripheral rim enhancement on gadolinium-enhanced. Further evaluation revealed a profoundly low serum cortisol (< 1.8 μg/dL) and low prolactin. This case underscores that a patient with adrenal insufficiency secondary to chronic pituitary apoplexy may present as hyponatremia with SIADH-like features.Bangladesh Crit Care J March 2026; 14 (1): 52-54